HASIL BELAJAR ANTARA MODEL PEMBELAJARAN SDM DAN GI DENGAN MEMPERTHATIKAN KEMAMPUAN BERKOMUNIKASI - Rini Ariyani; Pujiati Pujiati; Nurdin Nurdin (JEE (Jurnal Edukasi Ekobis), 2015)
This research was motivated by the low learning outcomes of Economicand review the comparison of the Economic learning results with cooperativelearning model of SDM and GI by observing the communication skills of studentsin class X SMA Negeri 1 Way Tenong. The results of the data analysis showedthat (1) There a difference of learning outcomes among students which learningwas using cooperative learning model SDM and GI type. (2) The results ofEconomics learning at students who have high ability to communicate whichlearning used SDM model was higher than those who used the GI model. (3) Theresults studied of Economics at students who have low ability to communicateusing the GI model was higher than learning of using SDM model. (4) There is aninteraction between cooperative learning model with the ability to communicatewith students on the subjects of Economics.Penelitian ini dilatarbelakangi oleh rendahnya hasil belajar Ekonomi serta mengkaji tentang perbandingan hasil belajar Ekonomi dengan model pembelajaran kooperatif SDM dan GI dengan memperhatikan kemampuan berkomunikasi siswa. pada kelas X SMA Negeri 1 Way Tenong. Hasil analisis data menunjukan (1) Terdapat perbedan hasil belajar Ekonomi antara siswa yang pembelajaran menggunakan model pembelajaran kooperatif tipe SDM dan tipe GI. (2) Hasil belajar Ekonomi pada siswa yang memiliki kemampuan berkomunikasi tinggi yang pembelajarannya menggunakan model SDM lebih tinggi dibandingkan yang pembelajarannya menggunakan model GI. (3) Hasil belajar Ekonomi pada siswa yang memiliki kemampuan berkomunikasi rendah yang pembelajarannya menggunakan model GI lebih tinggi dibandingkan yang pembelajarannya menggunakan model SDM. (4) Ada interaksi antara model pembelajaran kooperatif dengan kemampuan berkomunikasi siswa pada mata pelajaran Ekonomi.Kata kunci: hasil belajar, kemampuan berkomunikasi, SDM, GI